A single-cell landscape of triptolide-associated testicular toxicity in mice - Zhang, Wei; Xia, Siyu; Ou, Jinhuan; Cao, Min; Cheng, Guangqing; Li, Zhijie; Wang, Jigang; Yang, Chuanbin (Journal of pharmaceutical analysis, 2023)
Triptolide is a key active component of the widely used traditional Chinese herb medicine Tripterygium wilfordii Hook. F. Although triptolide exerts multiple biological activities and shows promising efficacy in treating inflammatory-related diseases, its well-known safety issues, especially reproductive toxicity has aroused concerns. However, a comprehensive dissection of triptolide-associated testicular toxicity at single cell resolution is still lacking. Here, we observed testicular toxicity after 14 days of triptolide exposure, and then constructed a single-cell transcriptome map of 59,127 cells in mouse testes upon triptolide-treatment. We identified triptolide-associated shared and cell-type specific differentially expressed genes, enriched pathways, and ligand-receptor pairs in different cell types of mouse testes. In addition to the loss of germ cells, our results revealed increased macrophages and the inflammatory response in triptolide-treated mouse testes, suggesting a critical role of inflammation in triptolide-induced testicular injury. We also found increased reactive oxygen species (ROS) signaling and downregulated pathways associated with spermatid development in somatic cells, especially Leydig and Sertoli cells, in triptolide-treated mice, indicating that dysregulation of these signaling pathways may contribute to triptolide-induced testicular toxicity. Overall, our high-resolution single-cell landscape offers comprehensive information regarding triptolide-associated gene expression profiles in major cell types of mouse testes at single cell resolution, providing an invaluable resource for understanding the underlying mechanism of triptolide-associated testicular injury and additional discoveries of therapeutic targets of triptolide-induced male reproductive toxicity. [Display omitted] •Triptolide-associated heterogenous DEGs in different cell types of mouse testes were identified.•Triptolide increases macrophages in mouse testes.•Apart from loss of germ cells, triptolides inhibits of germ cell development.•Triptolides inhibits pathways for spermatid developments in Leydig and Sertoli cells.